Upper pole access is safe and effective for pediatric percutaneous nephrolithotomy. Issue 2 (April 2018) - Oner, Sedat; Karagozlu Akgul, Ahsen; Demirbas, Murat; Onen, Efe; Aydos, Murat; Erdogan, Abdullah
Summary: Introduction: Upper pole access in percutaneous nephrolithotomy (PCNL) provides a straight tract to the ureter, resulting in easier placement of a guidewire to the ureter, good exposure of the pelvis, calices, and upper ureter, and comfortable manipulations. However, despite these benefits, upper pole access is usually avoided because of the risk of chest complications in both pediatric and adult patients. Objective: We aimed to evaluate the safety and morbidity of single upper pole access in pediatric patients undergoing PCNL. Study design: We retrospectively reviewed patients aged ≤17 years with renal stones who underwent PCNL with a single access between August 2004 and February 2016. The patients were separated into two groups: the single upper pole access group (SUPAG) and the single other pole access group (SOPAG). We compared the SUPAG and SOPAG in terms of the demographic features of the patients, stone burden and location, operative data, and postoperative outcomes. Complications were classified according to the modified Clavien system. Results: During the study period, 101 PCNL procedures were performed, 77 of which were managed with only one access. The median age of the 77 patients managed with a single access was 12 years (range 3–17 years). The number of cases in the SUPAG and SOPAG was 10 and 67, respectively. There were no statistically significant differences between the SUPAG and SOPAG in terms of age, sex, stone location, hydronephrosis status, stone area, side of kidney, and previous stone treatment or renal surgery. Furthermoret, there were no significant differences between the groups in terms of the operative parameters. Although the difference was insignificant, the median operation times in the SUPAG and SOPAG were 37 and 45 min, respectively. There was no chest complication or bleeding that required transfusion in the SUPAG. Two cases required transfusion, and one case was managed with a double pigtail catheter (double-J) placement because of prolonged extravasation in the SOPAG. The stone-free ratios were 100% and 82.1% in the SUPAG and SOPAG, respectively. Conclusion: Upper pole access provides similar outcomes to other (middle and lower) pole accesses, and may be performed without serious complications. These results indicate that this is a safe and effective approach of PCNL, and it presents a good alternative for removal of renal stones in pediatric patients.